(3ecGQe GdCNdGb heYGdjgG heMehO WQGFbgGs - (3eMeO Hf LYaQ Hf eMeO Hf Sgd CHh HcQ GdNQGFWj GdSGeQj , CHh HcQ,J (B327 (3g` s
(3ChdgG (B:s
(3Chd YfGhjfg(B: (3HGH eG jSJMH ef MSf GdUMHI ai GdSaQ s
(3BNQgG (B:s
(3eGjbhdg EPG Bhi Edi aQGTg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B224 - (3U(B237s
(3fSNI Ydjg SeGY eDQN SfI (B463s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B70 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B154s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B549 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B194 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1811s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI HOeTb (B(224/164) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs